The Relationship Between Quality Assurance Structure and Profitability in Iranian Pharmaceutical Industries - Abbas Kebriaeezade; Mohammad Sadegh Khoramirad; Meysam Seyedifar; Ali Homayouni (Tehran University of Medical Sciences, 2021)
Background: Quality Assurance Structure (QAS) plays an essential role in the profitability and market size of pharmaceutical companies. Accordingly, this study aimed to evaluate the quality certificates and QAS of pharmaceutical companies in Iran. Quality principles can increase consumer satisfaction, leading to elevated sales and profitability for companies. Besides, they have always been accompanied by growth and development. A well-established quality would be greatly valuable; if properly managed, it could influence the development of pharmaceutical companies. Methods: In this study, the data of sales, operating profit, quality certificates, organizational chart, and quality staff were received by companies. Moreover, we made appointments with each company and received the real data directly from the relevant officials. The quality certificates and relative percentage of quality staff were collected and compared with the domestic sales, exports, and operating profit of companies. Finally, the achieved results were analyzed to determine the relationship between financial and qualitative parameters. Results: The relationship between QAS and sales and corporate profitability was determined. The present study data indicated a relationship between the qualitative and financial sectors of pharmaceutical companies. Conclusion: Prior surveys and the obtained data suggested that quality structure and quality certificates significantly increase the domestic sale, export, and profitability of companies. However, numerous other parameters can also be involved in the sales volume of companies that require further investigations.